38.2: Distinguished Student Paper: High‐Efficiency Three‐Stack Tandem White OLEDs. Issue 1 (June 2015) - Son, Young Hoon; Lee, Jung Min; Kang, Byoung Yeop; Kwon, Jang Hyuk
Abstract : Three‐stack tandem white OLEDs made with fluorescent blue and phosphorescent red and yellow‐green materials are reported with 51 lm/W efficacy at 1000nit without out‐coupling, 7.4 V driving voltage, and 37, 000hr lifetime at 3000nit. With internal and external our‐coupling in this device, 100 lm/W efficiency is achieved.